Decreased expression of Ly-1 antibody reactive clone (Lyar) triggers enhanced adipogenesis of bone marrow mesenchymal stromal cells in aged bone marrow - Yu Shinyashiki; Yuta Onodera; Yusuke Kawashima; Natsumi Iwawaki; Toshiyuki Takehara; Koji Goto; Takeshi Teramura (PLoS ONE, 2026)
Accumulation of adipocytes within the bone marrow is a frequently observed during aging. However, the molecular mechanisms underlying aberrant adipocyte differentiation in aged bone marrow remain largely unclear.　In this study, we identified Ly-1 antibody reactive clone (Lyar) as an interacting partner of TGF-β activated kinase 1 (Tak1), a key molecule of non-canonical TGF-β signaling, through a proteomics approach, and demonstrated its involvement in the regulation of aging-related enhancement of adipogenesis. Lyar was not only implicated in the regulation of BMMSC proliferation but also may partly mediate the inhibitory effects of Bromodomain-containing protein 2 (Brd2). An age-associated decline in Lyar expression was associated with a reduction in FGF2–PI3K–Akt1 signaling activity in aged bone marrow. These findings suggest that Lyar may act as a context-dependent modulator of TGF-β signaling and may be involved in regulating proliferation and differentiation in BMMSCs. The age-related loss of Lyar may contribute to the complex mechanisms underlying enhanced adipogenesis in aged bone marrow, providing new insights into the regulation of mesenchymal stem cell fate during aging.